Penggunaan Metode Cotextual Teaching And Learning (CTL) Dalam Pembelajaran PPKn Di SDN Babadsari 1 - Fawaz, Andre; Farhurohman, Oman (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
The form of problems that are often faced by the world of education, especially learning Pancasila and Citizenship Education is the low interest of students in learning. One approach that must be developed to answer these problems is a contextual approach or contextual education and learning (CTL). The CTL approach is learning that helps teachers relate material to students' actual situations and encourages them to connect their knowledge in everyday life. This study aims to find out how the application of the Contextual Teaching and Learning (CTL) method is carried out at SDN Babadsari 1. This research uses a qualitative descriptive method. Data collection is done through observation, interviews, and documentation. Instruments in the form of observation, interviews, and document review. Based on the findings that have been made at SDN Babadsari 1 and previous research related to the use of the Contextual Teaching and Learning (CTL) method in improving learning outcomes, it is considered quite effective. The CTL approach requires students to connect the concepts studied with their situation.